PERAN UNIT APRON MOVEMENT CONTROL DALAM MENINGKATKAN KEAMANAN DAN KETERTIBAN DI AREA APRON BANDAR UDARA SUPADIO PONTIANAK KALIMANTAN BARAT - Peron, Peron; Mursyid, Mursyid (LPPM AKADEMI MANAJEMEN ADMINISTRASI YOGYAKARTA, 2024)
Every airport must of course pay more attention to security and order in the flight airside area and the apron area carried out by Apron Movement Control (AMC) Unit officers. The purpose of this research is to determine 1) the role of the AMC unit in improving security and order in the apron area of ??Supadio Airport, Pontianak, West Kalimantan; 2) problems faced by the AMC unit in improving security and order in the apron area of ??Supadio Airport, Pontianak, West Kalimantan; and 3) efforts that will be made by the AMC unit to overcome problems faced in carrying out its duties. This type of research is qualitative. In this research, data was collected using interview, observation and documentation techniques. The results of the research are 1) The AMC Unit has the task of being responsible for flight operational service activities, apron management and all interested people in the airside area in ensuring security and order in the apron area; 2) There are Ground Handling officers who are having problems, recruiting new employees and there is no special equipment to ensure the vehicle is safe; and 3) Efforts to overcome this problem include giving light punishments to officers, briefing new employees and merging with engineering units.